Pengaruh Pembelajaran Tahsin Al-Qur'an terhadap Pemahaman Kaidah Tajwid dan Kemampuan Hafalan Al-Qur'an pada Peserta Kelas Tahsin Ummahat Rumah Qur'an Ubay bin Ka'ab Unit Rasjida Nazief - Annisa Rahma Aulia; Sori Monang (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to examine the effect of Qur'anic tahsin learning on the understanding of tajwid rules and Qur'anic memorization ability among participants of the Ummahat Tahsin Class at Rumah Qur'an Ubay bin Ka'ab, Rasjida Nazief Unit. The study employed a quantitative correlational design involving 23 participants selected using a saturated sampling technique. Data were collected through a tahsin learning questionnaire, a tajwid comprehension test, a Qur'anic memorization performance assessment, and interviews as supporting data. Data analysis was conducted using IBM SPSS Statistics, including validity and reliability tests, descriptive statistics, normality and linearity tests, Pearson correlation, simple linear regression, and Spearman correlation. The results indicate that Qur'anic tahsin learning has no significant effect on participants' understanding of tajwid rules (r = 0.173; p = 0.426; R² = 0.030). In contrast, tahsin learning has a significant and strong effect on Qur'anic memorization ability (r = 0.647; p < 0.001). These findings suggest that tahsin instruction, which emphasizes talaqqi, repeated recitation, and direct teacher feedback, is more effective in improving memorization than theoretical understanding of tajwid. Therefore, integrating conceptual tajwid instruction with practical recitation is recommended to enhance both theoretical understanding and practical competence among adult learners.